Correlation of pulmonary function abnormalities with dose volume histograms in children treated with lung irradiation. Issue 6 (18th March 2014) - De, Aliva; Kamath, Sunil; Wong, Kenneth; Olch, Arthur J.; Malvar, Jemily; Sposto, Richard; Mascarenhas, Leo; Keens, Thomas G.; Venkatramani, Rajkumar
Summary Background There is limited data on pulmonary function test (PFT) abnormalities in children treated with modern irradiation techniques. PFT abnormalities have not been correlated with the dose and volume of irradiation. Methods A retrospective chart review of PFTs and clinical outcomes in children who received radiation therapy (RT) at Children's Hospital Los Angeles between 1999 and 2009 was performed. Radiation dose distribution to normal lung tissue was calculated. Results Forty‐nine patients had PFTs available post‐RT at a median time of 2.91 years (range, 0.01–8.28) from irradiation. Sixty‐seven percent of patients had at least one PFT abnormality on their last available study. The most common abnormality was obstructive lung disease (24%) followed by hyperinflation (20%). Thoracic surgery prior to RT increased the odds of an abnormal FEV1, RV/TLC, and obstructive disease. The sex of the patient, age at the time of irradiation, and time of the PFT after irradiation did not have a significant association with abnormalities. The mean lung dose, maximum lung dose, and prescribed dose of radiation were significantly associated with the development of PFT abnormalities. The odds of developing an abnormal PFT increased with increase in the minimum threshold dose (Vdose) of radiation, mostly above V20. Conclusion PFT abnormalities are common even when modern radiation techniques are used. A significant correlation between radiation parameters and PFT abnormalities was noted. Pediatr Pulmonol. 2015; 50:596–603. © 2014 Wiley Periodicals, Inc.